Anticoagulant therapy control in primary healthcare setting - Z. K. Salpagarova; D. A. Andreev; D. A. Sichev; A. A. Bikova; S. A. Syrkin; S. A. Suchkova (Сеченовский вестник, 2016)
The aim of the study was to evaluate eﬃciency anticoagulant therapy control in primary healthcare setting. The prospective, controlled study involved 301 patients with «non-valvular» atrial ﬁbrillation, receiving various anticoagulant drugs in 2013–2015. After discharge the patients were advised to visit anticoagulant therapy control department. The risk of thromboembolic complications and the risk of bleeding  were assessed with CHA2DS2VASc scale HAS-BLED, respectively. Major bleeding was assessed with TIMI scale. The time in therapeutic range for Warfarin  was assessed for the patient taking warfarin. The study involved 301 patients with non-valvular atrial ﬁbrillation taking anticoagulants: warfarin – 49 (16%), rivaroxaban – 34 (11%), apixaban – 81 (28%) and dabigatran –137 (45%). Minor bleeding was found in all groups. Large bleeding was found in patients receiving warfarin, dabigatran and rivaroxaban.